A Marginal Cost Model for the Hiring-Overtime Decision - Lundgren, Earl F.; Schneider, V. (Management Science, 1971)
In the case where a given demand increase over a finite time span is known and exceeds current production capacities, a marginal cost analysis can provide decision criteria for work-force adjustments. Using the marginal costs of hiring new workers and for various periods of overtime as a basis, decisions can be made to hire new workers, to work overtime, or to do both. The marginal cost analysis for hiring new workers includes the application of learning curve data to their increasing productivity rate over the time span. The approach minimizes costs, assuming it is not necessary to buy new equipment or add supervisors. The greatest applicability for the model may be found in certain job shop situations.